1989
DOI: 10.1152/ajpgi.1989.257.4.g601
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged ambulant monitoring of human colonic motility

Abstract: The study of human colonic motility under physiological conditions has proved to be an elusive goal. We have used a two-stage pernasal technique to position sensors in the human colon for the prolonged monitoring of motility in freely ambulant subjects. Nine healthy volunteers were studied for a total recording time of 263 h, each study lasting between 13 and 48 (mean 29) h. Motor activity in all regions of the large bowel was characterized by scant and irregular contractions with infrequent bursts that did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
35
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 0 publications
5
35
1
Order By: Relevance
“…This number is similar to that reported in two previous studies18 19 of colonic motility recorded using a lesser number of transducers introduced into the colon transnasally.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This number is similar to that reported in two previous studies18 19 of colonic motility recorded using a lesser number of transducers introduced into the colon transnasally.…”
Section: Discussionsupporting
confidence: 90%
“…Twenty four hour colonic motility has been studied in the prepared bowel,16 17 but relatively little information is available about coordinated pressure activity in the healthy unprepared colon over a prolonged period 1819 Our first aim was therefore to characterise this further.…”
mentioning
confidence: 99%
“…Results from the few previous studies using manometry in patients with idiopathic fecal incontinence have been contradictory. Some authors found an increased number of high amplitude colonic contractions while others did not [8,[25][26][27][28][29]. The results of our study of colorectal transport in idiopathic fecal incontinence are in accordance with those form another scintigraphic study by Herbst et al [8].…”
Section: Discussionsupporting
confidence: 90%
“…35 The method avoids the problem of colonoscopy in healthy volunteers, is well tolerated, but has some limitations. Firstly, it takes 24-60 hours for the tube to pass through the gut, a time that could be shortened by using a two stage per nasal technique to position the tube in the colon, as proposed by Soffer et al 34 Secondly, the subjects are not ambulatory, a condition that can reduce colonic motility.36 Thirdly, the method probably does not work in patients who have severe motor disorders because of decrease in the motility needed to propel the tube. Lastly, as with other colonic intubation techniques, it cannot be ruled out that the manometric tube may induce motor changes.…”
Section: Discussionmentioning
confidence: 99%